A target's perspective on the effects of ATPs in takeovers after recognizing its choice in the process - Goktan, M. Sinan; Kieschnick, Robert (Journal of Corporate Finance, 2012)
The use of antitakeover provisions (ATPs) in corporate charters/bylaws has evoked substantial debate over their costs and benefits. While there are many empirical studies of their effects in takeovers, these studies have ignored the self selection issues introduced by studying completed transactions, which reflect the target's choice. We examine data on a sample of U.S. corporations and show that accounting for self selection leads to a more nuanced understanding of how ATPs influence target shareholder wealth. We show that the effect of ATPs is more on the likelihood of receiving a bid rather than the success of a bid and that the success of a takeover is driven primarily by the characteristics of the offer and offer process rather than by the characteristics of the target and its ATPs. Further, we document that prior empirical studies that ignore these issues have mis-estimated the economic and statistical significance of various ATPs on target shareholder wealth.